"It's not a simple answer." A qualitative study to explore how healthcare providers can best support families with a child with autism spectrum disorder and overweight or obesity. Issue 14 (3rd July 2022) - McPherson, Amy C.; Perez, Arnaldo; Buchholz, Annick; Forhan, Mary; Ball, Geoff D. C.
Abstract: Purpose: This qualitative study aimed to explore the experiences of parents supporting their child with Autism Spectrum Disorder (ASD) and overweight or obesity (OW/OB), including their weight management support needs. Methods: Interview transcripts were analysed using inductive thematic analysis. Nine parents ( n = 9 mothers) of ten children with ASD (7 males, 3 females) participated in individual semi-structured interviews. Results: The three themes developed were: (1) Our journey to obtain weight management support; (2) I need real-world solutions; and (3) The what, who and how of our weight management needs. Parents reported being proactive in seeking weight management support for their child but were disappointed with the services offered. Resources were not tailored to the child's complex nutrition and behavioural issues or their abilities and functioning. A multidisciplinary approach that integrated both disability and weight management expertise was desired, but not experienced. A range of formal and informal programs were recommended. Conclusion: This study provides a call to action for supports that ensure children with ASD and OW/OB receive integrated, individualised support to maximise their health and wellness. Implications for rehabilitation: Children with autism spectrum disorder (ASD) are at high risk of developing overweight or obesity. The weight management support needs of parents of children with ASD and overweight or obesity are not being met. Support must be tailored to the child's needs, which are often complex. Health services that integrate expertise in both disability and weight management are needed for children with ASD and their families.